Penentuan Kualitas Kaolin sebagai Prekursor Sintesis Zeolit pada Kegiatan Praktikum - Ismail, Rohmat; Erlangga, Manasye; Himawan, Ari; Afiah, Givana Indah Nurul (Jurnal Pengelolaan Laboratorium Pendidikan, 2025)
Zeolite synthesis has attracted the attention of researchers today because of the functional properties of zeolites. The zeolite synthesis process can be influenced by various factors, one of which is the quality of the zeolite precursor. One of the precursor materials for zeolite synthesis is kaolin. This study aims to determine the quality of three kaolin brands used as precursors for zeolite synthesis in practicum activities. The quality of kaolin was assessed through gravimetric loss on ignition testing and analysis of the metal oxide composition using an X-ray fluorescence (XRF) spectrometer. The loss on ignition analysis results for kaolin A, kaolin B, and kaolin C samples were 7.94%, 7.87%, and 6.52%, respectively. The XRF analysis results, which included the compositions of SiO2, TiO2, Al2O3, Fe2O3, CaO, MgO, K2O and Na2O, were as follows: for kaolin A, 57.58%, 0.78%, 19.69%, 5.83%, 0.23%, 1.03%, 0.99% and 0.11%; for kaolin B, 56.30%, 0.80%, 21.30%, 7.19%, 0.08%, 0.52%, 1.19% and 0.16%; and for kaolin C, 68.03%, 0.80%, 14.40%, 5.08%, 0.32%, 0.94%, 0.95% and 0.01%. The two analysis results showed that the three kaolin samples had met the requirements as zeolite precursors based on the range of reference specification values: loss on ignitation<10%, SiO2 content 50–70%, TiO2 <1%, Al2O3 8.5–30.5%, Fe2O3 2–15.5%, CaO <1.68%, MgO 0.48–1.19%, K2O <3.6%, and Na2O <0.35%. The ensuing results furnish recommendations for the zeolite synthesis practicum, to select the most suitable kaolin type.